Early Childhood Education During the COVID-19 Outbreak: The Perceived Changing Roles of Preschool Administrators, Teachers, and Parents - Yildiz, Suleyman; Kilic, Gulenay Nagihan; Acar, Ibrahim H. (SPRINGER, 2023)
Stakeholders (teachers, preschool administrators, and parents) in early childhood education have struggled due to the COVID-19 outbreak. The present study explores the experiences and perceptions reflecting the perceived changes in the roles of stakeholders in early childhood education as a result of the COVID-19 pandemic in Turkey. A criterion sample of two administrators, nine teachers, and seven parents in early childhood education institutions was interviewed. We used Moustakas's (Phenomenological research methods, Sage, Thousand Oaks, 1994) phenomenological method to collect, analyze, and validate the data. The main themes showed that: (1) Stakeholders have experienced substantial challenges in online education; (2) The online delivery of instructional content has changed the administrators' financing and instructional leadership role; (3) Teachers have acquired new roles in some areas such as communication, content development, and technology use. In addition, the mentoring roles and social responsibilities of administrators and teachers have increased due to the COVID-19 pandemic; and (4) Supporting roles towards their children have been proliferated and diversified. Overall, findings from the present study provided insights into the stakeholders' perceived accumulated and altered roles in early childhood education because of the COVID-19 outbreak.
Keywords: Early childhood education; Administrative roles; COVID-19; Online education; Education & Educational Research